THE LANGUAGE ACQUISITION OF SENTENCES TYPES BY AUTISM CHILDREN OF PELITA HATI ELEMENTARY SCHOOL PALEMBANG - Tresiana Sari Diah Utami (Jurnal Didascein Bahasa, 2018)
This study entitled language acquisition of sentences types by autism children of Pelita Hati elementary school Palembang. The research problem is how far did the autism children acquire the language?. This Study aimed to describe the type of acquisition of sentence forms of autism children. It used descriptive method. The data was gained from these utterances; it was produced by the second graders of Pelita Hati Elementary School Palembang. The data was collected by observation, note taking, and recording. The result showed that all of sentences acquired by the students had achieved declarative, interogative, imperative sentence. Meanwhile, the exclamative sentences had not been acquired yet.Keywords: children with special needs, sentences.